2016
DOI: 10.5005/jp-journals-10024-1837
|View full text |Cite
|
Sign up to set email alerts
|

In vitro comparison of impact of different bleaching Agents on the microhardness of Enamel

Abstract: Background: Various agents are used these days for increasing the esthetics. One such procedure is bleaching that offers various advantages, as it is minimal invasive and cheap option to color the teeth and remove stain. The altered enamel after the bleaching process shows surface demineralization and porosities. The present study aimed to evaluate the effect of different bleaching agents on the microhardness of enamel. Materials and methods:A total of 100 freshly human extracted maxillary premolar teeth were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
(14 reference statements)
1
3
0
1
Order By: Relevance
“…In our study the specimen were exposed to 40 % HP. Our findings were in accordance with the results obtained by previous studies who noticed no enamel alteration after bleaching solution exposure ( 21 , 22 ). In this study there was significant difference between 24 hours and two months and hardness was higher in two months.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In our study the specimen were exposed to 40 % HP. Our findings were in accordance with the results obtained by previous studies who noticed no enamel alteration after bleaching solution exposure ( 21 , 22 ). In this study there was significant difference between 24 hours and two months and hardness was higher in two months.…”
Section: Discussionsupporting
confidence: 94%
“…It was concluded that increase in elastic modulus of bleached enamel could be achieved by post treatment. Bleaching procedures also involve different techniques with different composition of peroxides ( 21 ). Literature quotes numerous studies showing adverse effects of these agents on tooth microhardness ( 4 , 8 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, some studies suggest that saliva may partially lead to the replacement of the mineral loss caused by the bleaching treatment. 29 , 30 Basting, et al 31 (2005) reported that immersion in a solution similar to human saliva for two weeks after bleaching may increase microhardness of bleached enamel. Similar to previous findings, saliva could present a reformative effect on the microhardness loss in this study.…”
Section: Discussionmentioning
confidence: 99%
“…liberados ( 2 ). Asimismo, se pueden presentar posibles efectos adversos al tratamiento, como la alteración del esmalte con zonas desmineralizadas, porosidades, que incluso influyen en su microdureza ( 3,4 ). Sin embargo, otros estudios mencionan que no existen alteraciones en la microdureza, la rugosidad y la morfología de la superficie ( [5][6][7] ).…”
unclassified